Remote sensing image fusion - Alparone, Luciano; Aiazzi, Bruno; Baronti, Stefano; Garzelli, Andrea (Boca Raton, Florida : CRC Press, 2015)
A synthesis of more than ten years of experience, Remote Sensing Image Fusion covers methods specifically designed for remote sensing imagery. The authors supply a comprehensive classification system and rigorous mathematical description of advanced and state-of-the-art methods for pansharpening of multispectral images, fusion of hyperspectral and panchromatic images, and fusion of data from heterogeneous sensors such as optical and synthetic aperture radar (SAR) images and integration of thermal and visible/near-infrared images. They also explore new trends of signal/image processing.
Instructions for use -- Sensors and image data products -- Quality assessment of fusion -- Image registration and interpolation -- Multiresolution analysis for image fusion -- Spectral transforms for multiband image fusion -- Pansharpening of multispectral images -- Pansharpening of hyperspectral images -- Effects of aliasing and misalignments on pansharpening -- Fusion of images from heterogeneous sensors -- New trends of remote sensing image fusion -- Conclusions and perspectives.
Includes bibliographical references (pages 275-299) and index.
Keywords: Remote sensing; Image processing -- Digital techniques